DNMT1-maintained hypermethylation of Krüppel-like factor 5 involves in the progression of clear cell renal cell carcinoma - Fu, Rong-Jie (Cell Death Dis, 2017)
Clear cell renal cell carcinoma (ccRCC) is the major subtype of renal cell carcinoma (RCC) that is resistant to conventional radiation and chemotherapy. It is a challenge to explore effective therapeutic targets and drugs for this kind of cancer. Transcription factor Krüppel-like factor 5 (KLF5) exerts diverse functions in various tumor types. By analyzing cohorts of the Cancer Genome Atlas (TCGA) data sets, we find that KLF5 expression is suppressed in ccRCC patients and higher level of KLF5 expression is associated with better prognostic outcome. Our further investigations demonstrate that KLF5 genomic loci are hypermethylated at proximal exon 4 and suppression of DNA methyltransferase 1 (DNMT1) expression by ShRNAs or a methylation inhibitor 5-Aza-CdR can recover KLF5 expression. Meanwhile, there is a negative correlation between expressions of KLF5 and DNMT1 in ccRCC tissues. Ectopic KLF5 expression inhibits ccRCC cell proliferation and migration/invasion in vitro and decreases xenograft growth and metastasis in vivo. Moreover, 5-Aza-CdR, a chemotherapy drug as DNMTs’ inhibitor that can induce KLF5 expression, suppresses ccRCC cell growth, while knockdown of KLF5 abolishes 5-Aza-CdR-induced growth inhibition. Collectively, our data demonstrate that KLF5 inhibits ccRCC growth as a tumor suppressor and highlight the potential of 5-Aza-CdR to release KLF5 expression as a therapeutic modality for the treatment of ccRCC.